Ligand-assisted structure tailoring of highly luminescent Cu-In-Zn-S/ZnS//ZnS quantum dots for bright and stable light-emitting diodes - Zang, Shuaipu; Zhang, Xuhui; Sun, Yingying; Li, Ning; Wang, Lei; Li, Lin Song (Frontiers in Chemistry, 2022)
Harnessing environment-friendly and low-cost multinary Cu-In-Zn-S quantum dots (QDs) as emitters for light-emitting diodes (LEDs) has attracted great attention for display and lighting application. However, suboptimal QD structure is a huge obstacle, which results in serious nonradiative recombination and efficiency roll-off. Herein, we synthesized structure-tailored Cu-In-Zn-S/ZnS//ZnS QDs by improving the reactivity of shell growth by 2-ethylhexanoic acid (EHA) ligands. The EHA-assisted shell growth can boost an extended alloyed layer at the core-shell interface and a smoothed confinement barrier, which effectively passivate the interface defects and suppress Förster resonance energy transfer (FRET) process. These synthesized QDs display a bright photoluminescence emission (quantum yield of 83%) and a larger size of 8.4 nm. Moreover, the resulting LEDs based on the EHA-assisted QDs exhibit a maximum luminance of 8074 cd/m2, and a current efficiency of 7.3 cd/A with a low efficiency roll-off. Our results highlight a remarkable ligand strategy to tailor the QD structure for high performance QD-based LEDs.